PENGARUH SOSIALISASI PERPAJAKAN DAN KUALITAS PELAYANANPERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK BUMI DANBANGUNAN KECAMATAN AMONGGEDO KABUPATEN KONAWE - Jusbair Baheri; Muh. Nur; Tinas Saputra (STIE ENAM ENAM KENDARI, 2025)
This study aims to determine the effect of tax socialization and the quality of tax services on taxpayer compliance. The method used is quantitative, with a population of all land and building taxpayers in Amonggedo District, Konawe Regency of 5,867, while a sample of 99 taxpayers was taken using random sampling, the number of which was determined by the Slovin formula. Data collection was carried out using a questionnaire in the form of a questionnaire. Data analysis used descriptive statistical analysis, instrument testing, classical assumption testing, multiple linear regression, determination testing, and hypothesis testing using SPSS v. 27 for windows. The results of the study indicate that Tax Socialization and Tax Service Quality on Taxpayer Compliance have a positive and significant effect on Amonggedo District, Konawe Regency.